SAMSN1 causes sepsis immunosuppression by inducing macrophages to express coinhibitory molecules that cause T-cell exhaustion via KEAP1–NRF2 signaling - Yao Li; Tingting Li; Fei Xiao; Lijun Wang; Xuelian Liao; Wei Zhang; Yan Kang; Jing Ni (Chinese Medical Journal)
Abstract. Background:. Immunosuppression is closely related to the pathogenesis of sepsis, but the underlying mechanisms have not yet been fully elucidated. In this study, we aimed to examine the role of the Sterile Alpha Motif, Src Homology 3 domain and nuclear localization signal 1 (SAMSN1) in sepsis and elucidate its potential molecular mechanism in sepsis induced immunosuppression. Methods:. RNA sequencing databases were used to validate SAMSN1 expression in sepsis. The impact of SAMSN1 on sepsis was verified using gene knockout mice. Flow cytometry was employed to delineate how SAMSN1 affects immunity in sepsis, focusing on immune cell types and T cell functions. Clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9)-mediated gene editing in RAW264.7 macrophages enabled interrogation of SAMSN1’s regulatory effects on essential macrophage functions, including cell proliferation and phagocytic capacity. The mechanism of SAMSN1 in the interaction between macrophages and T cells was investigated using the RAW264.7 cell line and primary cell lines. Results:. SAMSN1 expression was significantly increased in patients with sepsis and was positively correlated with sepsis mortality. Genetic deletion of Samsn1 in murine sepsis model improved T cell survival, elevated T cell cytolytic activity, and activated T cell signaling transduction. Concurrently, Samsn1 knockout augmented macrophage proliferation capacity and phagocytic efficiency. In macrophage, SAMSN1 binds to Kelch-like epichlorohydrin-associated protein 1 (KEAP1), causing nuclear factor erythroid 2-related factor 2 (NRF2) to dissociate from the KEAP1–NRF2 complex and translocate into the nucleus. This promotes the transcription of the coinhibitory molecules CD48/CD86/carcinoembryonic antigen related cell adhesion molecule 1 (CEACAM1), which bind to their corresponding receptors natural killer cell receptor 2B4/CD152/T cell immunoglobulin and mucin domain-containing protein 3 (TIM3) on the surface of T cells, inducing T-cell exhaustion. Conclusions:. SAMSN1 deletion augmented adaptive T cell immunity and macrophage phagocytic-proliferative dual function. Furthermore, it mediates the KEAP1–NRF2 axis, which affects the expression of coinhibitory molecules on macrophages, leading to T-cell exhaustion. This novel immunosuppression mechanism potentially provides a candidate molecular target for sepsis immunotherapy.